2019
DOI: 10.1371/journal.pone.0223857
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, characteristics, and mortality of infective endocarditis in France in 2011

Abstract: ObjectivesWe assessed the determinants of mortality in infective endocarditis (IE), using the national hospital discharge databases (HDD) in 2011.MethodsIE stays were extracted from the national HDD, with a definition based on IE-related diagnosis codes. This definition has been assessed according to Duke criteria by checking a sample of medical charts of IE giving a predictive positive value of 86.1% (95% confidence interval (CI): 82.7% - 89.5%). The impact of heart valve surgery on survival has been studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
20
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 35 publications
8
20
0
2
Order By: Relevance
“…Twenty-seven per cent of patients underwent heart valve surgery. This was consistent with recent data on French epidemiology and a recent prospective study in older patients (mean age 83 years) showing that surgery was performed in 16% of cases (Sunder et al, 2019;Forestier et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Twenty-seven per cent of patients underwent heart valve surgery. This was consistent with recent data on French epidemiology and a recent prospective study in older patients (mean age 83 years) showing that surgery was performed in 16% of cases (Sunder et al, 2019;Forestier et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…The recent study in Spain demonstrated an increasing incidence of IE in pacemakers (22). CDRIE represented 27.4 % of all IE cases in our cohort, which is a substantially higher number compared to other reports from the European countries, including the overall results of EURO-ENDO registry (1,23,24). We may speculate, whether such high proportion of patients with CDRIE might have been affected by involvement of only tertiary care centres in our cohort, which 82 % (9/11) out of them possess Cardiac surgery department performing the most complicated cases, including lead extractions.…”
Section: Discussionmentioning
confidence: 48%
“…IE is well described in the general population [1,6,7]. There are also numerous reports in hemodialysis (HD) patients, where IE is reported as both frequent and deadly, with a 45.6% mortality [8][9].…”
Section: Discussionmentioning
confidence: 99%